Factors Of Influence Choice Of Warnet Locations In Koto Baru Villagers Of Dharmasraya Regency - NURSEHA, NURSEHA; DRS. Bakaruddin, Ms, DRS. Bakaruddin, Ms; Zuriyani, M.Si, Elvi (STKIP PGRI Sumbar, 2014)
Abstracts The purpose of this research to get data, process, analys, and investigetion about factors that influences the selection of internet kiosk locations in the koto baru villagers of darmasraya regency, like that :1. Level of education 2. Tools of infratructure 3. Social culture. The kind of this research is descriptive carrolation. Population krom this research is all of internet kiosk industrialist it koto baru villagers of darmasraya regency. The it esearcher taked respodence sample which total sampling base of persentation that 100% sample in koto baru villagers of darmasraya regency with 38 person. The analys from this research is deskriptive and inferencial satistik. The researcher finded some effect from this research, such as : ( 1 ) there are influence of level education to selection of internet kiosk in koto baru villagers of darmasraya regency, because t hitung > t tabel; ( 2,581 > 1,686 ) stranger of level education to section kiosk location is weak ( r=0,255) end constribution is big ( 6,5 % ) ( 2 ). There are influences tool of infrastructure to selection of internet kiosk location in koto baru villagers of darmasraya regency, because t hitung > t tabel; ( 3,399>1,666), stranger correlation tool of infrastructure to selection kiosk location is weak (r=0,0666) and contrubution is big ( 4%). (3) there are influences social culture to selection internet kiosk location in koto baru villagers of dharmasraya regency, because t hitung > t tabel; ( 2,952>1,686 ), stanger of social culture to selection kiosk locasion is weak ( r= 0,157 ) and contribution is big ( 2,5% ). (4). there are influence of education level, tool of imprastructure and social cultere is same for selection of internet kiosk location in koto baru villager of dharmasraya regency because f hitung > f tabel; ( 8,865 >2,88) , stranger of three variable correlation to selection of kiosk location is weak ( r= 0,266 ) and contribution from three variable is 7,1 %.